2019
DOI: 10.3390/ijerph16234663
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Total Nitrogen and Phosphorus Using Single or Combinations of Aquatic Plants

Abstract: Phytoremediation is a potentially suitable technology for taking up large amounts of N and P during plant growth and the removal of plant material, thereby avoiding eutrophication. We compared the capacity of nine different aquatic plant species for removing total P (TP), total N (TN), and NH4+-N from raw domestic sewage wastewater collected from a living area located in Guangzhou city, China, and different concentrations of artificial wastewater. The experiments were performed in two stages, namely screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 22 publications
1
22
0
1
Order By: Relevance
“…The wastewater pollution by excessive nitrogen (N) and phosphorus (P) has become a widespread global problem, leading to the degradation of aquatic ecosystems, a decline in biodiversity, the collapse of nutrient cycles, and the development of water blooms [ 2 , 3 , 4 ]. For example, eutrophication has caused negative effects on agricultural, industrial, and drinking water production [ 5 ]. To address these serious issues, various physical, chemical, and biological measures have been applied to remediate N and P pollution over the past several decades [ 6 , 7 , 8 ], including aeration, water diversion, sediment dredging, chemical flocculation, chemical algaecide addition, and in situ chemical reaction techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wastewater pollution by excessive nitrogen (N) and phosphorus (P) has become a widespread global problem, leading to the degradation of aquatic ecosystems, a decline in biodiversity, the collapse of nutrient cycles, and the development of water blooms [ 2 , 3 , 4 ]. For example, eutrophication has caused negative effects on agricultural, industrial, and drinking water production [ 5 ]. To address these serious issues, various physical, chemical, and biological measures have been applied to remediate N and P pollution over the past several decades [ 6 , 7 , 8 ], including aeration, water diversion, sediment dredging, chemical flocculation, chemical algaecide addition, and in situ chemical reaction techniques.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, multi-species systems should deliver good performance by buffering against variations in weather and nutrient conditions as a result of their diversity and adaptability [ 24 ]. Some studies have shown that multiple plants can purify water quality better than a single plant owing to a more reasonable species diversity, which makes it easier to maintain the long-term stability of the ecological system [ 5 , 25 ]. Coleman et al [ 26 ] found that the mixed planting of Schoenoplectus tabernaemontani , Juncus effusus , and Typha latifolia had a better purification effect on domestic sewage than a single species.…”
Section: Introductionmentioning
confidence: 99%
“…Eutrophication as a result of excessive nutrient levels can cause extensive population increases of macrophytes including duckweed (Lemnaceae) and harvesting of such organisms is suggested as a means of recycling nutrients (Quilliam et al, 2015; Su et al., 2019). Duckweed compete with algae and other aquatic species in the water column by reproducing as rapidly as possible (taking up nutrients as they do) to colonize the surface and shade out the plankton.…”
Section: Introductionmentioning
confidence: 99%
“…To address these serious issues, many conventional and novel methods using physical, chemical, and biological processes have been applied to treat animal wastewater over the past several decades [8,9]. Among these methods, phytoremediation using aquatic plants with high productivity and nutrient removal capability has received increasing public attention in recent years [10,11].In tropical and subtropical regions, free-floating macrophytes are the dominant vegetation used in wastewater restoration [4]. Numerous studies have documented their ability to remediate eutrophic water bodies [12], including the following positive attributes: (1) high productivity, (2) high nutritive value, and (3) ease of stocking and harvesting [13].…”
mentioning
confidence: 99%
“…To address these serious issues, many conventional and novel methods using physical, chemical, and biological processes have been applied to treat animal wastewater over the past several decades [8,9]. Among these methods, phytoremediation using aquatic plants with high productivity and nutrient removal capability has received increasing public attention in recent years [10,11].…”
mentioning
confidence: 99%